Comparative aspects of individual indicators of the physical development of primary school age children (Environment & Health, 2019)
Physical development is one of the leading health criteria that predetermine the necessity to perform population monitoring of the growth and formation processes in children.The purpose of the study was to determine the individual morphological indicators of 8 year old schoolchildren in Lviv, as well as to establish the differences between them and the anthropometric parameters of the children's population from urban agglomerations on the territory of other climatic-geographical zones of Ukraine and neighboring European states.Materials and methods. During 2015-2016 in accordance with the generally accepted methods of anthropometry, 2nd grade schoolchildren studying in municipal general education schools (GEEE) were surveyed. The study covered 459 children, among them 236 boys and 223 girls. The harmony of physical development was assessed by the value of the body mass index (BMI, Quetelet index, biomass index) as the ratio of body weight in kg to height in meters squared. In order to study the somatotype, the calculation of the proportionality index between the chest circumference and the body length according to M.V. Chernorutskyi was used.Results. On the basis of the conducted survey regression scales were developed for the evaluation of FD of 8 year old children. Among the surveyed urban 8 year old schoolchildren there is a predominance of a contingent of middle-height individuals; one third of children had a body length bigger or smaller than the specified range. Average values of BMI for children are in the range of 16.52 ± 0.42 kg / m² and 15.85 ± 0.38 kg / m² for boys and girls, respectively. A larger proportion of 8 year old schoolchildren (54.5%) have normosthenic built according to the proportionality index between the chest circumference and the body length. Comparison of BM and BL indicators of Lviv 8 year old schoolchildren with similar parameters of their peers in other countries (Poland, Belarus) indicates that there are no reliable differences. The established regularities indicate an increase in the anthropometric parameters of children in the southern and western regions in comparison with similar indicators of their peers living in the north, east and in the center of Ukraine.Conclusions. It is feasible to elaborate normative references of anthropometric parameters of children in accordance with the distribution of administrative units in the climatic-geographical zones and to take into account the active migration processes inherent in the present. The proposed normal reference ranges and the assessment of the level of FD in children should consist of 6 variants of regression scales or percentile charts and curves.
Keywords: primary school age children; physical development; height; body weight; chest circumference